2010
DOI: 10.1556/amicr.57.2010.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 in chronic hepatitis C patients

Abstract: Liver fibrosis (LF), where the chronic HCV infection is a major cause, is a characteristic of chronic liver diseases. LF results from chronic damage to the liver in conjunction with the accumulation of ECM proteins. Matrix metalloproteinases (MMPs) and their specific inhibitors (TIMPs) are thought to play an essential role in the hepatic lesions. The available data concerning the circulating levels of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in chronic hepatitis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
3
17
0
4
Order By: Relevance
“…Diverse intensity and progression of airway inflammation between studied COPD groups could be responsible for these discrepancies. As has been shown in patients with liver diseases, those with chronic hepatitis C exhibited high serum MMP-9 concentrations, which decreased to the nadir in subjects with liver cirrhosis, while TIMP-1 concentrations significantly increased, serving as a marker of fibrotic changes [25]. This suggests that the proteases/antiproteases balance may depend on and change with the progression of disease.…”
Section: Discussionmentioning
confidence: 80%
“…Diverse intensity and progression of airway inflammation between studied COPD groups could be responsible for these discrepancies. As has been shown in patients with liver diseases, those with chronic hepatitis C exhibited high serum MMP-9 concentrations, which decreased to the nadir in subjects with liver cirrhosis, while TIMP-1 concentrations significantly increased, serving as a marker of fibrotic changes [25]. This suggests that the proteases/antiproteases balance may depend on and change with the progression of disease.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to MMP-2, MMP-9 levels show their value primarily in the diagnosis of hepatocellular carcinoma [62]. In one of the studies, MMP-9 levels were negatively correlated to the histological severity of the liver disease in patients with chronic hepatitis C [63]. …”
Section: Diagnostics Of Acquired Liver Fibrosismentioning
confidence: 99%
“…For example, chronic hepatitis C causes the elevation of both TIMP-1 and TIMP-2 in corollary with fibrosis progression [60]. A recent study of the relationship between serum MMP-9, TIMP-1 and fibrosis in 50 patients with various chronic liver disease showed that serum levels of MMP-9 in chronic hepatitis patients were low as compared to the controls ( P < 0.05) [63]. Moreover, serum MMP-9 levels decrease as chronic hepatitis progresses to cirrhosis, while TIMP-1 levels increase along with an increase of the degree of fibrosis (r = 0.73, P < 0.001).…”
Section: Diagnostics Of Acquired Liver Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Some genes were found to play critical roles in these processes, including MMP9, TIMP1 and STAT1 [8-11]. However, the spectrum of temporal pathway deregulation has rarely been studied using a systematic framework.…”
Section: Introductionmentioning
confidence: 99%